Comparative analysis of 333 proGAV® and proGAV 2.0® adjustable valves in pediatric hydrocephalus treatment: survival and complication rate assessment - Issa, Mohammed; Paggetti, Filippo; Dannehl, Clara; Ueding, Nieke; Krieg, Sandro; El Damaty, Ahmed (Acta neurochirurgica, 2024)
ProGAV and ProGAV2.0 adjustable valves are extensively used for treating hydrocephalus in pediatric patients. This study aims to conduct a comprehensive comparison between these two valves concerning their survival and complication rates.
Online veröffentlicht: 9. November 2024
Gesehen am 18.06.2025